Dual-Channel Chaos Synchronization in Two Mutually Injected Semiconductor Ring Lasers - Ruiyi Tang; Zaifu Jiang; Dingmei Zhang; Jinhui Wang (Photonics)
A chaotic synchronization system based on two mutually injected semiconductor ring lasers (SRLs) is constructed and the synchronization performance is analyzed. First, based on the symmetric theory, three types of chaos synchronization, isochronal chaos synchronization between the same modes (ICSS), isochronal chaos synchronization between different modes (ICSD), and leader-laggard chaos synchronization between different modes (LLCSD) are identified. Then, the performance of the three types of synchronization is investigated by cross-correlation technology. The results show that, with the appropriate feedback and injection parameters, all three synchronization structures can achieve high-quality chaos synchronization. Among them, ICSS can achieve high-quality synchronization under various parameters, while ICSD and LLCSD require larger injection and feedback parameters to achieve a comparable synchronization quality. Finally, the impact of a parameter mismatch on three types of synchronization quality is studied, and the results showed that the LLCSD has a stronger robustness than ICSS and ICSD. Therefore, under larger injection and feedback parameters, LLSCD is the preferred structure for synchronization communication in SRL. The research results can provide a theoretical reference for the application of SRLs in chaotic secure communication.